A new Cd based metal–organic framework for quick and convenient detection of trace water in isopropanol and 1, 4-dioxane. Issue 45 (6th November 2018) - Cheng, Feng; Fu, Ruibiao; Wen, Yuehong; Yang, Yu-Ying; Zeng, Chen; Zhang, Yuxiao; Hu, Shengmin; Wu, Xintao
Abstract : A Cd-MOF that can be used for rapid and convenient detection of trace amounts of water in Isopropanol and 1, 4-dioxane. Abstract : A new Cd-MOF ([Cd(py)(L)(H2 O)2 ], 1 ) based on a fluorescent brightener (Na2 L, disodium 4, 4′-bis(2-sulfonatostyryl)biphenyl) was synthesized by a hydrothermal method.1 emits weak fluorescence, but it can partially dissociate in a few seconds when encountering water, releasing L 2− ligands with a strong luminescence. The luminescent color of the L 2− aqueous solution is different from that of L 2− in other organic solvents, which makes1 capable of detecting trace amounts of water in isopropanol and 1, 4-dioxane. Compared to the MOFs currently used to detect trace amounts of water in organic solvents, 1 is simpler to produce, cheaper in raw materials and higher in sensitivity (v/v, <0.01%). Furthermore, a test paper has been made from1 for the rapid detection of trace amounts of water. And the detection process has no special requirements of the surrounding environment, making1 a rapid sensor for trace amounts of water in organic solvents.